Early embryo achievement through isolated microspore culture in Citrus clementina Hort. ex Tan., cvs. ‘Monreal Rosso’ and ‘Nules’ - Chiancone, Benedetta; Karasawa, Marines M. Gniech; Gianguzzi, Valeria; Abdelgalel, Ahmed M.; Bárány, Ivett; Testillano, Pilar S.; Marinoni, Daniela Torello; Botta, Roberto; Germanà, Maria Antonietta (Frontiers in Plant Science, 2015)
Microspore embryogenesis is a method of achieving complete homozygosity from plants. It is particularly useful for woody species, like Citrus, characterized by long juvenility, a high degree of heterozygosity and often self-incompatibility. Anther culture is currently the method of choice for microspore embryogenesis in many crops. However, isolated microspore culture is a better way to investigate the processes at the cellular, physiological, biochemical and molecular levels as it avoids the influence of somatic anther tissue. To exploit the potential of this technique, it is important to separate the key factors affecting the process and, among them, culture medium composition and particularly the plant growth regulators and their concentration, as they can greatly enhance regeneration efficiency. To our knowledge, the ability of meta-Topolin, a naturally occurring aromatic cytokinin, to induce gametic embryogenesis in isolated microspores of Citrus has never been investigated. In this study, the effect of two concentrations of meta-Topolin instead of benzyladenine or zeatin in the culture medium was investigated in isolated microspore culture of two genotypes of Citrus. After eleven months of isolated microspore culture, for both genotypes and for all the four tested media, the microspore reprogramming and their sporophytic development was observed by the presence of multinucleated calli and microspore-derived embryos at different stages. Microsatellite analysis of parental and embryo samples was performed to determine the embryo alleles constitution of early embryos produced in all tested media, confirming their origin from microspores. To our knowledge, this is the first successful report of Citrus microspore embryogenesis with isolated microspore culture in Citrus, and in particular in Citrus clementina Hort. ex Tan, cvs. ‘Monreal Rosso’ and ‘Nules’.